INCLUSIVE SOCIETY: CONCEPTUAL AND PHILOSOPHICAL ANALYSIS (Scientific journal of the Fergana State University, 2026)
This article discusses the concept of an inclusive society, the experience of foreign countries in the areas of social development, equal opportunities and ensuring a sustainable environment, as well as the philosophical aspects of national experience. Theoretical analysis of the concept of an inclusive society and concepts of inclusive development, reforms being carried out in Uzbekistan on an inclusive society, and the processes of socio-economic growth with inclusive social indicators in foreign countries are discussed.